Intraductal papillary mucinous neoplasm of the intrahepatic bile duct: a review of literature and a rare case report - Zibari, Lehat; Naseer, Muhammad S.; Patel, Het; Shokouh-Amiri, Hosein; Wellman, Gregory; Dies, David; Browne, Veron; Zibari, Gazi B. (Frontiers in Surgery, 2023)
Background Intraductal papillary neoplasm of the bile duct is a rare variant of bile duct tumors, which is characterized by papillary or villous growth inside the bile duct. Having papillary and mucinous features such as those found in pancreatic intraductal papillary mucinous neoplasm (IPMN) is extremely rare. We report a rare case of intraductal papillary mucinous neoplasm of the intrahepatic bile duct. Case report A 65-year-old male Caucasian with multiple comorbidities presented to the emergency room with moderate constant pain at the right upper quadrant (RUQ) abdomen for the last several hours. On physical examination, he was found to have normal vital signs, with icteric sclera and pain on deep palpation at the RUQ region. His laboratory results were significant for jaundice, elevated liver function tests and creatinine, hyperglycemia, and leukocytosis. Multiple imaging studies revealed a 5 cm heterogeneous mass in the left hepatic lobe that demonstrated areas of internal enhancement, mild gall bladder wall edema, dilated gall bladder with mild sludge, and 9 mm common bile duct (CBD) dilatation without evidence of choledocholithiasis. He underwent a CT-guided biopsy of this mass, which revealed intrahepatic papillary mucinous neoplasm. This case was discussed at the hepatobiliary multidisciplinary conference, and the patient underwent an uneventful robotic left partial liver resection, cholecystectomy, and lymphadenectomy. Conclusion IPMN of the biliary tract may represent a carcinogenesis pathway different from that of CBD carcinoma arising from flat dysplasia. Complete surgical resection should be performed whenever possible because of its significant risk of harboring invasive carcinoma.